2001
DOI: 10.1057/palgrave.jmm.5040053
|View full text |Cite
|
Sign up to set email alerts
|

Brand medicine: Use and future potential of branding in pharmaceutical markets

Abstract: Successful pharmaceutical companies are rich in intellectual property. Historically, this property has taken the form of patents, and a company's skill in acquiring such assets has been instrumental in driving its share price. But with the huge increase in public interest in and access to hitherto restricted pharmaceutical products and information, it is clear that the industry's approach to marketing must change. Couple this with the increasing elusiveness of breakthrough new products, and it becomes clear th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 0 publications
0
32
0
5
Order By: Relevance
“…8 A strong base of loyal consumers would give additional time to maximise the return on investment. 9 The explanation is relatively straightforward: patent expiry often coincides with peak sales for a product, and therefore, at its simplest, for every month a pharmaceutical brand with annual sales of $1.2bn is maintained, the revenue upside is $100m. A six-month delay is therefore worth over $0.5bn.…”
Section: Brand Name Strategiesmentioning
confidence: 99%
“…8 A strong base of loyal consumers would give additional time to maximise the return on investment. 9 The explanation is relatively straightforward: patent expiry often coincides with peak sales for a product, and therefore, at its simplest, for every month a pharmaceutical brand with annual sales of $1.2bn is maintained, the revenue upside is $100m. A six-month delay is therefore worth over $0.5bn.…”
Section: Brand Name Strategiesmentioning
confidence: 99%
“…Blackett and Harrison, 2001;Ryder, 2004;Webster, 2000). It creates an intimate bond with customers based on its value proposition or a brand promise (Barnes, 2003;Muniz and O'Guinn, 2001).…”
mentioning
confidence: 99%
“…Given today's technology and sciences, when a new molecule discovery is made, which is more effective for a certain treatment, existing brands lose their importance 6 . Weston has suggested that 'super brands' are capable of surviving patent expiration and can achieve "a bond with the consumer at a level transcending mere functional performance" 15 .…”
Section: What Are the Differences Between Pharmaceutical And Fast-movmentioning
confidence: 99%
“…The value is recognised as one of the most vital part of branding, which in itself has three types: functional, expressive and central values. Normally, successful brands have a combination of value types 3,[6][7] .…”
mentioning
confidence: 99%